DEVELOPING BLENDED LEARNING MODEL USING SCHOOLOGY-BASED FLIPPED CLASSROOM ROTATION FOR PRACTICING SELF-REGULATED LEARNING ABILITY - Alvin Nadiroh; Ahmad Lubab; Aning Wida Yanti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This research is aimed to develop lesson plan (RPP) with a blended learning model in rotation of flipped classrooms and teaching materials packed into schoology to practice self-regulated learning skills in a valid and practical application. The form of the lesson plan integrates self-regulated learning aspects into learning activities to practice the students’ self-regulated learning skills. The learning material is arranged into two types: interesting reading books in PDF and animated PPT (Ms.PowerPoint) slides. The whole of the materials, discussions, and exercises are included in schoology. The topics discussed in this research are sine and cosine rules. The research applies the 4D (Define, Design, Develop, Disseminate) model of research and development. The subjects of the research are 38 students of X Science 5 of MAN 2 Gresik. The data of the research is collected by field-note and validation sheets, then analyzed with the field-note data analysis techniques, validity, and practicality of the learning media. The result of the research shows that the developed lesson plan is reached the eligibility standard based on the validity and practicality of the learning media. The validity score of the lesson plan is 4,52 on average with the highly valid category, and the validity score of learning materials in schoology is 4,48 with the highly valid category. The experts stated that the lesson plans and teaching materials in schoology that were developed were feasible with an average value of "A" which means that the learning tools developed are practical and can be applied without revision.Penelitian ini bertujuan untuk mengembangkan RPP model pembelajaran blended learning dengan rotasi flipped classroom dan bahan ajar yang dikemas dalam schoology guna melatih kemampuan self-regulated learning yang valid dan praktis digunakan. RPP disusun dengan mengintegrasikan aspek-aspek self-regulated learning dalam kegiatan pembelajaran agar dapat melatih kemampuan self-regulated learning siswa. Bahan ajar disusun dalam dua bentuk yaitu buku bacaan menarik berupa PDF dan animasi PPT. Seluruh materi pada bahan ajar, diskusi, dan latihan soal dimuat di dalam media schoology. Materi yang digunakan dalam perangkat pembelajaran adalah aturan sinus dan cosinus. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian pengembangan dengan model pengembangan 4D (Define, Design, Develop, Disseminate). Subjek penelitian ini adalah siswa kelas X IPA 5 MAN 2 Gresik berjumlah 38 siswa. Instrumen pengumpulan data pada penelitian ini adalah lembar field note (catatan lapangan) dan lembar validasi. Data penelitian ini kemudian dianalisis menggunakan teknik analisis data field note, kevalidan perangkat pembelajaran, dan kepraktisan perangkat pembelajaran. Hasil dari penelitian ini menunjukkan bahwa perangkat pembelajaran yang dikembangkan memenuhi standar kelayakan. Hal ini berdasarkan hasil kevalidan dan kepraktisan perangkat pembelajaran yang dikembangkan. Hasil kevalidan RPP diperoleh rata-rata 4,52 dengan kriteria sangat valid, dan hasil kevalidan bahan ajar dalam schoology diperoleh rata-rata 4,48 dengan kriteria sangat valid. Para ahli menyatakan bahwa RPP dan bahan ajar dalam schoology yang dikembangkan layak untuk digunakan dengan rata-rata nilai “A” yang artinya perangkat pembelajaran yang dikembangkan praktis dan dapat digunakan tanpa revisi.